"We're just teaching in a vacuum". Teaching in context in the learning for sustainability project - Eureta Janse van Rensburg (Environmental Association of Southern Africa, 1998)
Learning for Sustainability is a Danish-funded project for supporting teachers in environmental education curriculum development, in the Departments of Education in the Gauteng and Mpumalanga provinces of South Africa. The Rhodes University Environmental Education Unit is responsible for its evaluation. Instead of establishing baseline data against which to compare the project outcomes, the researchers are developing contextual profiles towards a deepening understanding of the contexts in which the teachers work, and to judge the appropriateness of project activities. This paper introduces insights from the developing profile based on questionnaires; interviews; observations during project meetings and school visits; and document analysis. The emerging issues pertain to curriculum and professional development in environmental education, within the context of educational policy transformation. In particular the paper highlights the role of context in responsive reform initiatives.